Comparative analysis of economic load dispatch using evolutionary and nature based algorithms - Sharma, Apratim; Vadhera, Shelly (2017 International Conference on Power and Embedded Drive Control (ICPEDC), 2017)
Economic load dispatch problem involves various equality and inequality constraints which makes it complex. This paper presents a comparative study between Particle swarm optimization and Gravitational search algorithm to analyze the Economic load dispatch problem for three and six unit system. The role of heuristic optimization methods in solving the economic load dispatch problem has been highlighted in this paper. Recently, researchers are paying more attention towards these heuristic optimization methods techniques to solve Economic Load Dispatch problem in order to find out optimal scheduling while meeting the transmission and operation constraints. Comparison have been made in terms of robustness and optimal search behavior.